Facile Synthesis of Hybridized Mesoporous Au@TiO2/SnO2 as Efficient Photocatalyst and Selective VOC Sensor. Issue 12 (9th August 2016) - Malik, Ritu; Tomer, Vijay K.; Chaudhary, Vandna; Dahiya, Manjeet S.; Rana, Pawan S.; Nehra, S. P.; Duhan, Surender
Abstract: Considering the novelty of heterojunction formation in sunlight photocatalysis, dahlia flower resembling Au loaded TiO2 /SnO2 nanocomposite was synthesized using facile hydrothermal method to improve the degradation rate of waste water pollutants. The intrinsic high surface area coupled with unique heterojunction formation causes Au@TiO2 /SnO2 to exhibit excellent photocatalytic activity towards the degradation of Rhodamine B (RhB) dye under sunlight irradiation. Under the optimized conditions of catalyst dosage (0.3 g/L), dye concentration (100 ppm) and pH (10), 99.2 % of the RhB aqueous solution was degraded in 35 min of illumination time. Moreover, the resulting Au@TiO2 /SnO2 nanohybrid unveiled excellent sensing response (43) towards acetone gas (100 ppm) while detecting a variety of common volatile organic compounds (VOCs) including methanol, benzyl alcohol and isopropanol at 220 °C. Thus, the enhanced photocatalytic activity for degrading organic pollutants under sunlight irradiation and excellent sensing properties at relatively lower working temperature, make this porous nanohybrid a promising candidate for environmental monitoring applications. Abstract : The schematic diagram is demonstrating the mechanism of photodegradation of Au@TiO2 /SnO2 for Rhodamine B under visible light irradiation